Humanizing Business through Emotions: On the Role of Emotions in Ethics - Lurie, Yotam (Journal of business ethics, 2004)
Emotions have not received sufficient attention in business ethics. This paper identifies the positive role of emotions in human judgment and attitudes. It then argues that emotions as well as feelings on the part of managers and their employees can be positive forces for both business managers and for the organizations they lead. Allowing emotions a stronger role in business affairs could serve in putting a more human face on both managers and their organizations.